On the (τ^2,τ)-Arcs in PG(2,qq) for τ≤qq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
In this article the existence of the arcs in the projective plane of order  has been proved. For  we have shown that the arcs are complete. The existence of the completes (144,12)-arc in , (256,16)-arc in  and - (324,18)arc in  have been found.